AIP Conference Proceedings 2009
DOI: 10.1063/1.3266793
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach to the Coronal Heating Problem

Abstract: The heating of the solar corona is discussed within both frameworks of kinetic and fluid drift wave theory. It is shown that the basic ingredient necessary for the heating is the presence of the background density gradients in the direction perpendicular to the magnetic field vector These gradients are a source of free energy for the electrostatic instabilities. Strongly growing modes are found for some typical coronal plasma parameters. The instabilities a) imply the presence of electric fields that can accel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…The wavelength parallel to the magnetic field vector is taken as λ z = s • 10 4 m. We have introduced a parameter s that we can vary within the range 10 −1 − 10 3 in order to demonstrate that the mode behavior remains unchanged at various density scale lengths L n , provided that we keep the ratio λ z /L n constant. It can easily be shown that in this case the ratio γ/ω r also remains constant [19,20], while both quantities are shifted either to lower or higher values. As example, the mode frequency for s = 1, L n = 100 m, and λ y = 1 m is ω r = 231 Hz, and it changes as 231/s when the other parameters are fixed.…”
Section: Model and Resultsmentioning
confidence: 78%
“…The wavelength parallel to the magnetic field vector is taken as λ z = s • 10 4 m. We have introduced a parameter s that we can vary within the range 10 −1 − 10 3 in order to demonstrate that the mode behavior remains unchanged at various density scale lengths L n , provided that we keep the ratio λ z /L n constant. It can easily be shown that in this case the ratio γ/ω r also remains constant [19,20], while both quantities are shifted either to lower or higher values. As example, the mode frequency for s = 1, L n = 100 m, and λ y = 1 m is ω r = 231 Hz, and it changes as 231/s when the other parameters are fixed.…”
Section: Model and Resultsmentioning
confidence: 78%